2019
DOI: 10.1186/s13041-019-0468-x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation induces gradual increases in the thickness and curvature of postsynaptic density of hippocampal CA1 neurons in slice cultures

Abstract: Activity can induce structural changes in glutamatergic excitatory synapses, including increase in thickness and curvature of the postsynaptic density (PSD); these structural changes can only be documented by electron microscopy. Here in organotypic hippocampal slice cultures where experimental conditions can be easily manipulated, increases in thickness and curvature of PSDs were noticeable within 30 s of stimulation and progressed with time up to 3 min. These structural changes were reversible upon returning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…The idea agrees well with the association of PSDL with Homer1 and GKAP, which are localized in between PSD-95 and shank layers (Tao-Chen, 2014. Shank is localized in the PSD pallium region and spine cytoplasm (Tao- Cheng, 2010Cheng, , 2019, and our immunogold histochemistry suggested that the PSDL structure is an underground structure in both PSD core and pallium. However, Shank amount is very low in the purified PSDL.…”
Section: Non-mec Proteins and Their Possible Roles For Psdlsupporting
confidence: 87%
“…The idea agrees well with the association of PSDL with Homer1 and GKAP, which are localized in between PSD-95 and shank layers (Tao-Chen, 2014. Shank is localized in the PSD pallium region and spine cytoplasm (Tao- Cheng, 2010Cheng, , 2019, and our immunogold histochemistry suggested that the PSDL structure is an underground structure in both PSD core and pallium. However, Shank amount is very low in the purified PSDL.…”
Section: Non-mec Proteins and Their Possible Roles For Psdlsupporting
confidence: 87%
“…Undoubtedly, if this aspect has to be addressed the use of a 3D reconstruction of the spine head becomes the preferential form of analysis [ 45 ]. Conversely, the high resolution 2D TEM micrographs of spine heads are extremely useful to measure PSD length and thickness [ 46 , 47 , 48 ], and curvature [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The architecture of the PSD, in terms of size and shape is important to determine both synapse activity and maturation stage. Whereas its thickness, area and the height of the synaptic cleft can vary as a function of activity [ 14 , 15 , 16 ], the transition from macular to perforated and, sometimes, fragmented PSD has been reported to reflect the shift from immature to mature synapse [ 2 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…These changes could be due to the increased fusion of vesicles that would result in a growth of the postsynaptic membrane, or to changes in the cytoskeleton caused by the calcium influx (for a detailed description of the possible mechanisms responsible for the changes in curvature, see [195]). Furthermore, another study showed that synaptic stimulation increased the curvature of the PSD, making it more convex [196], however, the characterization of synaptic curvature in this study (as in [189,190,193]) was performed in single sections instead of 3D reconstructions, which could be misleading, since the curvature of a single synapse can change from one section to another [195].…”
Section: Curvature Of the Synaptic Apposition Surfacesmentioning
confidence: 92%